Perceptions of Students on the Islamic Religious Education Programme Regarding the Course on Learning Evaluation - Hilya Camelia Fathma; Ifina Adila Azza; Pipit Ertika Daristin (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2026)
The paradigm shift in learning evaluation requires students not only to understand the concept of evaluation but also to be able to implement it in learning practice. This study aims to describe the perceptions of students on the Islamic Religious Education programme regarding the Learning Evaluation course. The study employed a quantitative descriptive approach, with data collected via a questionnaire distributed to 11 fourth-semester students selected through purposive sampling. The data were analysed using descriptive analysis techniques. The results indicate that the majority of students held positive perceptions of the ‘Learning Assessment’ course. Students demonstrated a good understanding of the functions, principles and role of assessment in learning and felt that the learning process and the lecturer’s explanations helped them to understand the design and application of assessment instruments. Nevertheless, the students’ level of readiness to implement learning evaluation in teaching practice remains in the ‘fairly ready’ category. These findings indicate a gap between the students’ conceptual mastery and their practical readiness to carry out learning evaluation. Therefore, it is necessary to strengthen practice-based learning through simulations, microteaching and exercises in designing evaluation instruments so that the students’ evaluative competencies can develop more optimally